2015
DOI: 10.1159/000441091
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Xanthine Oxidase Activity Is Predictive of Cardiovascular Disease in Patients with Chronic Kidney Disease, Independently of Uric Acid Levels

Abstract: Background: Chronic kidney disease (CKD) is associated with increased cardiovascular morbidity and mortality. Oxidative stress seems to play a pivotal role in this process, and purine metabolism may be involved in CKD-related oxidative stress. Xanthine oxidase (XO) is an enzyme involved in purine metabolism and is also responsible for the production of reactive oxygen species. Methods: This prospective study aimed to analyze the relation between plasma dosages of molecules involved in redox balance, purine met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 33 publications
2
62
0
1
Order By: Relevance
“…This result is in line with the report by Otaki et al, in which eGFR of "low XOR" group (53 ± 25 mL/min/1.73 m2) was significantly lower than that of "normal XOR" group (68 ± 26 mL/min/1.73 m2) [21]. On the other hand, Gondouin et al reported the "increase" of XOR activity in accordance with renal dysfunction [31]. To measure XOR activity, Gondouin et al used the "classical method", in which XOR activity is measured as urate level after administration of xanthine to the specimen.…”
Section: Discussionsupporting
confidence: 91%
“…This result is in line with the report by Otaki et al, in which eGFR of "low XOR" group (53 ± 25 mL/min/1.73 m2) was significantly lower than that of "normal XOR" group (68 ± 26 mL/min/1.73 m2) [21]. On the other hand, Gondouin et al reported the "increase" of XOR activity in accordance with renal dysfunction [31]. To measure XOR activity, Gondouin et al used the "classical method", in which XOR activity is measured as urate level after administration of xanthine to the specimen.…”
Section: Discussionsupporting
confidence: 91%
“…47 In fact, a recent study of patients with CKD demonstrated that plasma xanthine oxidase activity is predictive of CVDs independently of UA levels. 48 Taken together, these results suggested that allopurinol may confer benefits to reduce the risk factors for cardiovascular disease independent of its UA-lowering effect.…”
Section: Discussionmentioning
confidence: 86%
“…Indeed, a previous study in a cohort of hypertensive nephropathy patients with impaired kidney function indicated that the use of allopurinol appears to be beneficial in preventing cardiovascular morbidity and all‐cause mortality without a significant influence on serum UA, suggesting that the benefits of allopurinol may be independent of its UA‐lowering effect . In fact, a recent study of patients with CKD demonstrated that plasma xanthine oxidase activity is predictive of CVDs independently of UA levels . Taken together, these results suggested that allopurinol may confer benefits to reduce the risk factors for cardiovascular disease independent of its UA‐lowering effect.…”
Section: Discussionmentioning
confidence: 86%
“…32) However, in these two studies, increased risk in subjects with low and high SUA was shown (J-shaped); therefore, the pattern differed from our observation (inverse J-shaped). Considering that an inverse J-shaped association was present only in female patients, it may suggest that not SUA per se, but other related factors, such as xanthine oxidase activity, 33) might explain the observed link between SUA and LVH. This possibility needs to be examined in future studies.…”
Section: Discussionmentioning
confidence: 91%